Sale and purchasing of toys in Malaysian night market. - Yasuo, K.; Said, A.M.; Chiong, H.N. (Malaysian Consumer and Family Economics Association, 2010)
The National Consumer Policy of Malaysia 1999 was formed to enhance consumer well-being through self-protection, self-regulation and the regulatory provisions by the government. However, the Government is yet to establish a comprehensive system of product safety that covers all types of consumer products in the market place such as toys. Although toys can be used to promote children's cognitive, motor, language, social and emotional development, they also present hazards if they are not selected and used appropriately. With a vast selection of types of toys, brands and models available to the consumers and the 2007 episodes of massive toys recall, it is pertinent that toy safety standards and guidelines are put in place. In this vein, an exploratory market study was undertaken to evaluate the circumstances of toys sale in Malaysian night markets. Data were collected using interview survey of the stall owners and the purchasers of toys at selected night markets. Descriptive statistics related to types, models, price range, country of origin of toys and reasons for purchasing are presented. Safety concerns and ways to enhance consumer protection against unsafe toys are discussed.